Exploration of the effects of Coriolis force and thermal radiation on water-based hybrid nanofluid flow over an exponentially stretching plate - A. S. Oke; B. C. Prasannakumara; W. N. Mutuku; R. J. Punith Gowda; B. A. Juma; R. Naveen Kumar; O. I. Bada (Scientific Reports, 2022)
Abstract Hybrid nanofluids’ enhanced thermophysical properties make them applicable in a plethora of mechanical and engineering applications requiring augmented heat transfer. The present study focuses on a three-dimensional Copper-Aluminium Oxide $$\left( Cu\text{- }Al_{2}O_{3}\right)$$ C u - A l 2 O 3 -water based hybrid nanofluid flow within the boundary layer with heat transfer over a rotating exponentially stretching plate, subjected to an inclined magnetic field. The sheet rotates at an angular velocity $$Ω$$ Ω and the angle of inclination of the magnetic field is $$γ$$ γ . Employing a set of appropriate similarity transformation reduces the governing PDEs to ODEs. The resulting ODEs are solved with the finite difference code with Shooting Technique. Primary velocity increases at large rotation but the secondary velocity reduces as the rotation increases. In addition, the magnetic field is found to oppose the flow and thereby causing a reduction in both the primary and secondary velocities. Increasing the volume fraction reduces the skin friction coefficient and enhances the heat transfer rate.